2006
DOI: 10.1177/0743558406293964
|View full text |Cite
|
Sign up to set email alerts
|

Late Adolescent Girls’ Sexual Experiences and Sexual Satisfaction

Abstract: This study presented and tested a model of sexual satisfaction for late adolescent girls. In this model, sexual self-concept and approach sexual motives were tested as predictors of adolescent girls’ sexual satisfaction with their most recent experience of sexual intercourse. A total of 116 girls in 12th grade (ages 16-19) completed measures of sexual self-concept and sexual experiences. A smaller number of girls (n = 70) with intercourse experience completed measures of their motives for engaging in sex and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 36 publications
7
100
1
3
Order By: Relevance
“…Fewer than 5% of the respondents reported any physiological dissatisfaction, and fewer than 8% reported any psychological dissatisfaction. Given the ubiquity of cultural messages disdaining sexual activity among young people, especially young women, the presence of sexual satisfaction both in this study and in 2 earlier studies of adolescents 31,36 is surprising and encouraging. Despite significant bivariate gender differences across a number of covariates (e.g., orgasm frequency, sexual guilt, self-esteem), both young women and young men in this study who had chosen to engage in partnered heterosexual activity reported considerable enjoyment with their sexual lives.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Fewer than 5% of the respondents reported any physiological dissatisfaction, and fewer than 8% reported any psychological dissatisfaction. Given the ubiquity of cultural messages disdaining sexual activity among young people, especially young women, the presence of sexual satisfaction both in this study and in 2 earlier studies of adolescents 31,36 is surprising and encouraging. Despite significant bivariate gender differences across a number of covariates (e.g., orgasm frequency, sexual guilt, self-esteem), both young women and young men in this study who had chosen to engage in partnered heterosexual activity reported considerable enjoyment with their sexual lives.…”
Section: Discussionmentioning
confidence: 74%
“…6,7 Adolescent girls' lack of pleasure is considered normative, whereas adult women are assumed to possess desire, and a failure in this regard may lead to a diagnosis of sexual dysfunction. 31,34 Despite this focus on negative sexual health, several studies of young people and sexual satisfaction do exist. 35 Auslander et al used a 7-item scale to examine sexual satisfaction among 313 sexually active 14-to 24-year-old participants from an adolescent medicine clinic.…”
Section: What We Know About Sexual Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have shown that positive sexual self-esteem is also associated with increased sexual satisfaction (Impett and Tolman 2006), frequent sexual communication (Oattes and Offman 2007), and safe sexual practices (Breakwell and Millward 1997;Lou et al 2010). To date, much of the research on sexual selfesteem has primarily been centered on the experiences of adolescents and sexual self-esteem's impact on adolescents' sexual risk-taking behaviors.…”
Section: Sexual Self-esteemmentioning
confidence: 99%